Effect of oxidation processing on the surface properties and floatability of Meizhiyou long-flame coal. (15th December 2017) - Chen, Songjiang; Tang, Longfei; Tao, Xiuxiang; Chen, Liang; Yang, Zhao; Li, Lulu
Highlights: After oxidation processing, the floatability of coal almost decreased exponentially along with the increasing concentration of H2 O2 solution. The active functional groups of >CH2 (1437 cm −1 ), CH3 (1373 cm −1 ) and COC (1215 cm −1 ) were susceptible to oxidation and oxygen-containing functional groups showed a significant increase. More holes and cracks were observed on the coal surface after oxidation processing. The poor flotation performance of oxidized coals may be attributed to dramatic changes in both surface chemical structure and surface morphology in oxidation process. Abstract: The surface properties of coal play a crucial role in its flotation, therefore it is of great significance to investigate the changes in both chemical structure and surface morphology in oxidation process of low rank coal. In this paper, the mechanism of difficult floatation of oxidized coal was highlighted. The surface hydrophobicity and floatability of Meizhiyou long-flame coal before and after oxidation processing with H2 O2 solution at different concentration were evaluated by induction time and contact angle analyses as well as flotation tests, while the changes in its surface properties in the oxidation process were analyzed by XPS, FTIR, BET and SEM measurements. The maximum increase extent of induction time between bubbles and oxidized coal particles reached to 13217% while the maximum reduction extent of combustible matter recovery reached to 95.28%, which indicated the floatability of oxidized coal particles almost decreased exponentially along with the increase of concentration of H2 O2 solution. Additionally, the results suggested the active chemical functional groups of >CH2 peak at 1437 cm −1, CH3 peak at 1373 cm −1 and COC peak at 1215 cm −1 were susceptible to oxidation. After oxidation processing, on the one hand, the content of hydrophobic groups on coal surface showed an obvious decrease while that of hydrophilic groups showed a significant increase. What's more, the content of carbonyl group had a close correlation with the extent of oxidation of the coal sample. On the other hand, it was found that the surface morphology of coals was significantly changed after oxidation process, and there were more pores and cracks on the coal surface. As a result, the contact angle of coals showed a significant decline after oxidation processing and it declined more quickly with the increase of contact time. Consequently, the poor flotation performance of oxidized coals may be attributed to the dramatic changes in both surface chemical structure and surface morphology in oxidation process.